PENGARUH LAYANAN PERSIAPAN PERSALINAN TERHADAP PENURUNAN TINGKAT KECEMASAN IBU HAMIL DI WILAYAH KERJA UPT PUSKESMAS ALAS BARAT KABUPATEN SUMBAWA - Fitri Setianingsih; Nurlaiala Agustikawati; Yunita Lestari (Pusat riset dan Inovasi Nasional, 2022)
A woman who is in pregnancy often experiences many changes, both physical changes and psychological changes. These changes can cause anxiety and increase anxiety. In third trimester pregnant women, the level of anxiety becomes more serious and intensive along the birth time schedule. Feelings of anxiety can cause tension in the mind and physique, pelvic muscles and lower uterine segment muscles; thus, this tension can disrupt the birth process. The impact of anxiety is so big for the mother and the fetus, so the interventions are needed to reduce anxiety in pregnant women. The purpose of this research was to find the effect of birthing preparation services. The research approach used a quantitative approach with preexperimental research design. This design involved pretest and posttest one group design. Samples in this study was 69 third trimester pregnant women. The data collection technique used a questionnaire was taken before experiment and after experiment. Data analysis used paired T test. The results showed that there was a significant difference in the level of anxiety between before and after being given pregnancy preparation services with (p value = 0.000) (p value = 0.000) or (p <0.05).